Positive pole piece as well as preparation method and application thereof
By using AS resin and polyvinyl butyral as composite binders in the positive electrode sheet of lithium-ion battery, combining carbon nanotubes and porous carbon-graphene composite materials as conductive agents, the PVDF binder is solved at high voltage The problem of poor downcycling performance improves the stability and mechanical properties of the battery, extends the battery life and prevents electrolyte corrosion.
Patent Information
- Application Number
- CN202411447274.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The commonly used PVDF adhesives in the positive electrode sheet of lithium-ion battery have poor high voltage resistance and weak bonding ability, resulting in poor cycling performance of the battery under high voltage and are prone to corrosion with the electrolyte, affecting the stability of the battery.
AS resin and polyvinyl butyral are used as composite binders, and carbon nanotubes and porous carbon-graphene composite materials are combined as conductive agents to form an efficient conductive network, enhance adhesion and mechanical properties, and protect the positive electrode materials from Corroded by electrolyte.
It improves the cycle stability and mechanical properties of the battery, enhances the high-voltage resistance of the electrode, extends the service life of the battery, and effectively prevents corrosion and parasitic reactions of the electrolyte.
Smart Images

Figure BDA0005088057880000151 
Figure BDA0005088057880000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode sheet and a preparation method and application thereof. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in smart phones, wearable devices, consumer drones, electric vehicles and other fields due to their high energy density, long cycle life and no memory effect. With the widespread application of lithium-ion batteries in the above fields, the market has higher and higher requirements for the performance of lithium-ion batteries.
[0003] However, the binder commonly used in the positive electrode of lithium-ion batteries is PVDF (polyvinylidene fluoride). PVDF has poor high-voltage resistance, and polyvinylidene fluoride is bonded to other parts of the electrode through weak van der Waals force interaction formed by F atoms. The bonding ability is weak, and the conductivity of the entire electrode is low. Therefore, it is not only unsuitable for high-voltage systems, but also affects the battery's cycle performance.
[0004] Therefore, it is necessary to provide a positive electrode plate that can adapt to high voltage systems, has high structural stability, has excellent electrical conductivity and can improve the cycle stability of the battery. Summary of the invention
[0005] The object of the present invention is to provide a positive electrode plate and a preparation method and application thereof. The positive electrode plate adopts AS resin and polyvinyl butyral as a composite binder, which can not only effectively bond and protect the positive electrode material from corrosion by the electrolyte, but also improve the mechanical properties of the positive electrode plate, thereby further improving the cycle performance of the battery.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising a positive electrode active layer, the positive electrode active layer comprising a positive electrode active material, a composite binder and a composite conductive agent;
[0008] The composite binder comprises AS resin and polyvinyl butyral.
[0009] Preferably, the mass ratio of the AS resin to polyvinyl butyral is (2:8) to (7:3), preferably (4:6) to (6:4).
[0010] Preferably, the composite conductive agent comprises a first conductive agent and a second conductive agent, the first conductive agent comprises carbon nanotubes and / or carbon fibers, and the second conductive agent comprises a porous carbon-graphene composite material.
[0011] Preferably, in the composite conductive agent, the content of the second conductive agent is 30-70wt%.
[0012] Preferably, the first conductive agent comprises carbon nanotubes and carbon fibers;
[0013] Preferably, in the composite conductive agent, the mass ratio of the carbon nanotubes to the carbon fibers is (2:8) to (8:2).
[0014] Preferably, the delithiation cut-off potential of the positive electrode active material is ≥4.4V.
[0015] Preferably, the positive electrode active material includes any one of a lithium nickel manganese oxide material, a lithium-rich manganese-based positive electrode material, lithium cobalt oxide or a ternary positive electrode material, or a combination of at least two thereof.
[0016] Preferably, the mass ratio of the positive electrode active material, the composite binder and the composite conductive agent is (80-97):(1.5-10):(1.5-10).
[0017] In a second aspect, the present invention provides a method for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0018] (1) mixing a positive electrode active material, a composite binder, a composite conductive agent and a solvent to obtain a positive electrode slurry;
[0019] (2) Coating the positive electrode slurry described in step (1) on at least one side of the current collector to obtain the positive electrode sheet.
[0020] In a third aspect, the present invention provides a battery, comprising the positive electrode plate as described in the first aspect.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention adopts AS resin and polyvinyl butyral as composite binders. On the one hand, the AS resin has a large number of nitrile groups, which can form hydrogen bonds with active materials to achieve effective bonding, and can form a uniform nano coating on the surface of positive electrode particles to protect the positive electrode material from electrolyte corrosion and prevent parasitic reactions. In addition, the phenyl group in the AS resin has strong mechanical strength, which helps to improve the mechanical strength of the electrode and slow down the expansion of the active material, thereby facilitating the improvement of battery cycle performance and improving the ion conductivity and thermodynamic properties of the composite binder. On the other hand, polyvinyl butyral can make the pole piece have good flexibility and avoid the brittle piece problem caused by the AS resin. DETAILED DESCRIPTION
[0023] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0024] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0026] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0028] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0029] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S12 and S14, which means that the method may include steps S12 and S14 performed sequentially, or may include steps S14 and S12 performed sequentially. For example, it is mentioned that the method may also include step S16, which means that step S16 may be added to the method in any order, for example, the method may include steps S12, S14 and S16, or may include steps S12, S16 and S14, or may include steps S16, S12 and S14, etc.
[0030] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0031] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0032] In existing positive electrodes, fluorine-based binders such as PVDF are mostly used to bond the positive electrode active materials and conductive agents. PVDF and other parts of the electrode are bonded through weak van der Waals forces formed by F atoms, and the bonding ability is weak, resulting in poor battery cycle performance.
[0033] The present invention provides a positive electrode plate, which adopts a composite binder with strong bonding force, and can effectively solve the problem of poor cycle performance caused by using a binder with insufficient bonding force in the positive electrode.
[0034] In one embodiment, the present invention provides a positive electrode plate, the positive electrode plate includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, a composite binder and a composite conductive agent;
[0035] The composite adhesive comprises AS resin and PVB (polyvinyl butyral), wherein the AS resin refers to a copolymer of styrene / acrylonitrile.
[0036] The present invention adopts AS resin and polyvinyl butyral as composite binders. On the one hand, the AS resin has a large number of nitrile groups, which can form hydrogen bonds with active materials to achieve effective bonding, and can form a uniform nano coating on the surface of positive electrode particles to protect the positive electrode material from electrolyte corrosion and prevent parasitic reactions. In addition, the phenyl group in the AS resin has strong mechanical strength, which helps to improve the mechanical strength of the electrode and slow down the expansion of the active material, thereby facilitating the improvement of battery cycle performance and improving the ion conductivity and thermodynamic properties of the composite binder. On the other hand, polyvinyl butyral can make the pole piece have good flexibility and avoid the brittle piece problem caused by the AS resin.
[0037] The parasitic reaction described in the present invention refers to the decomposition of the electrolyte to produce HF due to the presence of trace water in the electrolyte, and the HF reacts with the positive electrode to continue to generate water, thereby causing the electrolyte to continue to decompose and continuously produce HF, resulting in continuous deterioration of battery performance.
[0038] In one embodiment, the mass ratio of the AS resin to polyvinyl butyral is (2:8) to (7:3), for example, 2:8, 4:6, 6:4 or 7:3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably (4:6) to (6:4).
[0039] When the mass ratio of the AS resin to the polyvinyl butyral of the present invention is too small, that is, when the AS resin is too little, the bonding ability of the composite binder decreases, and a uniform nano-scale coating cannot be formed on the surface of the positive electrode particles. When the mass ratio is too large and the AS resin is too much, the disadvantage is that the prepared positive electrode plate becomes brittle and the cycle performance deteriorates.
[0040] In one embodiment, the composite conductive agent includes a first conductive agent and a second conductive agent, the first conductive agent includes CNT (carbon nanotube) and / or VGCF (carbon fiber), and the second conductive agent includes PCG (porous carbon-graphene composite material).
[0041] The present invention adopts a variety of conductive agents to form point, line and surface multi-dimensional contact with active materials, thereby constructing an efficient and stable conductive network, reducing the internal resistance of the battery, reducing polarization, and extending the battery life.
[0042] The porous carbon-graphene composite material of the present invention refers to a material in which porous carbon particles are generated on graphene through a chemical reaction. The preparation method comprises: mixing phenolic resin with potassium chloride, drying, carbonizing, acid washing, and washing with water to obtain the porous carbon-graphene composite material.
[0043] The carbon particles on the porous carbon-graphene composite material can play a good barrier role, preventing the agglomeration of graphene and carbon nanotubes and / or carbon fibers, ensuring the uniformity and stability of the conductive slurry, thereby effectively ensuring the conductivity of the composite conductive agent, which is beneficial to the rapid transmission of lithium ions in the positive electrode.
[0044] In addition, since the present invention adopts a composite binder, after adopting the composite binder, a composite binder coating will be formed on the surface of the positive electrode active material particles, which will inevitably affect the electronic conductivity of the positive electrode, and will also lead to poor cycle performance and increased polarization. Therefore, the present invention uses a composite conductive agent to effectively solve this problem.
[0045] In one embodiment, in the composite conductive agent, the content of the second conductive agent is 30-70wt%, for example, 30wt%, 40wt%, 50wt%, 60wt% or 70wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In one embodiment, the first conductive agent includes carbon nanotubes and carbon fibers, and the composite conductive agent includes carbon nanotubes, carbon fibers and a porous carbon-graphene composite material.
[0047] In one embodiment, in the composite conductive agent, the mass ratio of the carbon nanotubes to the carbon fibers is (2:8) to (8:2), for example, 2:8, 4:6, 6:4 or 8:2, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] In one embodiment, the lithium desorption cut-off potential of the positive electrode active material is ≥4.4V, for example, 4.4V, 4.6V, 4.8V or 4.9V, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] In one embodiment, the positive electrode active material includes any one of a nickel manganese oxide material, a lithium manganese-rich positive electrode material, lithium cobalt oxide, or a ternary positive electrode material, or a combination of at least two thereof.
[0050] In one embodiment, the mass ratio of the positive electrode active material, the composite binder and the composite conductive agent is (80-97):(1.5-10):(1.5-10), for example, it can be 80:10:10, 85:5:10, 90:5:5 or 97:1.5:1.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] It is understandable that the use of high-voltage active materials to prepare positive electrodes is one of the main means of improving the energy density of batteries in this field. However, the use of high-voltage active materials brings two new technical problems. First, the battery prepared from high-voltage active materials must be used at a high working voltage. On the one hand, the existing positive electrode binders are generally fluorine binders such as PVDF. In long-term high-voltage cycles, fluorine binders such as PVDF will gel and swell in the liquid electrolyte, further resulting in reduced contact between active material particles, thereby causing the battery capacity to decay rapidly. On the other hand, fluorine binders such as PVDF have weak bonding ability, which is not conducive to the performance of battery performance. Second, under high-voltage working conditions, active materials are prone to side reactions with electrolytes, causing electrolyte decomposition, and most of the transition metal ions contained in high-voltage active materials will be released, and reduction reactions will occur at the negative electrode, all of which will lead to deterioration of the battery's cycle performance.
[0052] In the present invention, by using a high-voltage positive electrode active material in combination with a composite binder, on the one hand, the composite binder is relatively resistant to high voltage and its performance does not change during long-term cycles. On the other hand, the composite binder of the present application can form a uniform nano-coating on the surface of the positive electrode particles to protect the positive electrode material from corrosion by the electrolyte. The nitrile group and the like can also complex with the transition metal ions to prevent the dissolution of transition metal ions in the positive electrode sheet and the occurrence of a reduction reaction on the negative electrode side, thereby destroying the SEI film on the negative electrode side, causing it to continuously regenerate and consume lithium ions in the battery, leading to the degradation of the battery cycle performance.
[0053] In the present invention, by using a high-voltage positive electrode active material in conjunction with a composite conductive agent, the problem of using carbon black or the like as a single conductive agent in a traditional positive electrode to induce electrolyte decomposition under high voltage, thereby causing battery cycle performance degradation, is effectively avoided. The composite conductive agent can also form point, line, and surface multi-dimensional contacts with the positive electrode active material, thereby constructing an efficient and stable conductive network. The prepared high-voltage positive electrode has no edge cracking, brittleness, or broken band problems, and has good cycle stability.
[0054] On the other hand, the composite binder forms a uniform nano-coating on the surface of the positive electrode particles, which can effectively improve the side reaction between the positive electrode active material and the electrolyte, but to a certain extent, it affects the lithium ion transmission of the positive electrode plate. The composite conductive agent forms multi-dimensional contact with the positive electrode active material in points, lines, and surfaces, which can effectively improve this problem. The combined use of the composite conductive agent and the composite binder can effectively build an efficient lithium ion and electron conduction network in the positive electrode.
[0055] In one embodiment, the positive electrode plate further includes a current collector, and the positive electrode active layer is disposed on one side or both sides of the current collector.
[0056] In a preferred embodiment, the current collector is selected from metal foil and composite current collector; the composite current collector has a sandwich structure similar to a sandwich, the middle polymer layer is mainly a polymer insulating resin and other materials, and the metal layer is deposited on both sides of the middle polymer layer by electroplating, chemical plating or other methods. Schematically, the polymer resin includes polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyether ether ketone, polyimide, polyamide, polyethylene glycol, polyamide-imide, polycarbonate, cyclopentane One or more of polyolefin, polyphenylene sulfide, polyvinyl acetate, polytetrafluoroethylene, polymethylene naphthalene, polyvinylidene fluoride, polyethylene naphthalate, polypropylene carbonate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), silicone, vinylon, polypropylene, polyethylene, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyphenylene ether, polyester, polysulfone and its derivatives, sodium carboxymethyl cellulose, styrene-butadiene rubber, fluorinated rubber, polyvinyl alcohol or polyvinylidene fluoride, etc. The material of the metal layer is selected from at least one of aluminum, copper, nickel, cobalt, tungsten, tin, lead, iron, silver or gold.
[0057] In a preferred embodiment, the current collector is aluminum foil.
[0058] In one embodiment, a method for preparing a positive electrode sheet is provided, the method comprising the following steps:
[0059] (1) mixing a positive electrode active material, a composite binder, a composite conductive agent and a solvent to obtain a positive electrode slurry;
[0060] (2) Coating the positive electrode slurry described in step (1) on at least one side of the current collector to obtain the positive electrode sheet.
[0061] In one embodiment, the thickness of the composite positive active electrode material layer may be 30 μm-400 μm, for example 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm-110 μm.
[0062] In one embodiment, a battery is provided, the battery comprising the positive electrode plate.
[0063] In one embodiment, the battery includes an electrolyte, and the electrolyte includes an electrolyte salt and a solvent.
[0064] In one embodiment, the electrolyte salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorooxalatoborate) (LiODFB), lithium difluorobis(oxalatophosphate) (LiODFP) or lithium tetrafluorooxalatophosphate (LiTFOP).
[0065] In one embodiment, based on the total mass of the electrolyte being 100%, the mass percentage of the electrolyte salt is 0.5-25%.
[0066] In one embodiment, the solvent includes: at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0067] In one embodiment, the electrolyte contains additives, and the electrolyte also includes additives, and the additives include at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, tris(triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid nitrile, and sebaconitrile.
[0068] In one embodiment, the battery further includes a negative electrode.
[0069] In one embodiment, the negative electrode includes a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector, wherein the negative electrode active material layer includes at least a negative electrode active material and a negative electrode binder.
[0070] In one embodiment, the negative electrode active material in the embodiment of the present application is not particularly limited, as long as it is a material that can electrochemically absorb and release S-zone metal ions such as lithium ions, sodium ions, potassium ions, and magnesium ions, such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These materials can be used alone, or two or more can be used in combination.
[0071] In one embodiment, a carbon material can be selected as the negative electrode active material, and specifically one or more of the following can be selected: graphite, needle coke, amorphous carbon, a carbon-containing mesophase, carbon fiber, and a carbon material with a low degree of graphitization. Among them, graphite can include natural graphite, artificial graphite, etc. In addition, materials obtained by coating them with carbon materials, such as amorphous carbon and graphitized materials, can also be used. Amorphous carbon includes but is not limited to particles obtained by firing the entire mesophase, and particles obtained by infusible treatment and firing of a carbon precursor. As carbonaceous particles with a low degree of graphitization, particles obtained by firing organic matter at a temperature generally below 2500°C can be listed.
[0072] In one embodiment, non-metallic materials that can be used as negative electrode active materials also include silicon and its compounds, such as Si, SiOx (0≤x<2). Since silicon-containing materials are prone to expansion, easy to fall off from the negative electrode current collector, and have poor conductivity, they are often mixed with carbon materials, such as a core-shell structure containing a carbon coating layer.
[0073] In one embodiment, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0074] In one embodiment, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95-97%.
[0075] In one embodiment, when the negative electrode active material is a non-metallic material such as a carbon material, the negative electrode binder may be an aqueous binder such as one or more of sodium hydroxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymer, cyclodextrin, etc.;
[0076] In one embodiment, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry. The negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying. The thickener can generally be used to adjust the viscosity of the slurry.
[0077] In one embodiment, the thickener in the embodiment of the present application can be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and their salts, etc.
[0078] In one embodiment, the mass proportion of the thickener in the negative electrode slurry can be 0.1-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5-3%, and more preferably 0.6-2%.
[0079] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0080] Example 1
[0081] This embodiment provides a positive electrode plate, the positive electrode plate comprising a current collector and a positive electrode active layer on both sides of the current collector, the positive electrode active layer comprising a positive electrode active material, a composite binder and a composite conductive agent in a mass ratio of 96.5:2:1.5;
[0082] The positive electrode active material is LiNiMnO4, and its lithium desorption cut-off potential is 4.9V;
[0083] The composite binder comprises AS resin and polyvinyl butyral in a mass ratio of 4:6, wherein the AS resin comprises styrene-acrylonitrile copolymer;
[0084] The composite conductive agent comprises a porous carbon-graphene composite material, carbon nanotubes and carbon fibers in a mass ratio of 5:3:2;
[0085] The current collector is aluminum foil;
[0086] The method for preparing the positive electrode sheet comprises the following steps:
[0087] (1) Weighing the positive electrode active material, the composite binder, and the composite conductive agent according to the mass ratio, adding the composite binder to the solvent NMP, mixing evenly, adding the positive electrode active material and the composite conductive agent and continuing to mix until a uniform state is formed to form a positive electrode active slurry;
[0088] (2) The positive electrode active slurry formed in step (1) is uniformly coated on the current collector to form the positive electrode sheet.
[0089] Example 2
[0090] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the AS resin to the polyvinyl butyral is 2:8.
[0091] Example 3
[0092] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the AS resin to the polyvinyl butyral is 7:3.
[0093] Example 4
[0094] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the AS resin to the polyvinyl butyral is 4:6.
[0095] Example 5
[0096] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the AS resin to the polyvinyl butyral is 6:4.
[0097] Example 6
[0098] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the porous carbon-graphene composite material, carbon nanotubes and carbon fibers is 3:5:2.
[0099] Example 7
[0100] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the porous carbon-graphene composite material, carbon nanotubes and carbon fibers is 7:2:1.
[0101] Example 8
[0102] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the composite conductive agent is a porous carbon-graphene composite material and carbon nanotubes in a mass ratio of 6:4.
[0103] Example 9
[0104] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the composite conductive agent is a porous carbon-graphene composite material and carbon fiber in a mass ratio of 6:4.
[0105] Example 10
[0106] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the AS resin to the polyvinyl butyral is 1:9.
[0107] Embodiment 11
[0108] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the AS resin to the polyvinyl butyral is 9:1.
[0109] Example 12
[0110] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the porous carbon-graphene composite material, the carbon nanotubes and the carbon fibers is 8:1:1.
[0111] Embodiment 13
[0112] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1 except that the mass ratio of the porous carbon-graphene composite material, the carbon nanotubes and the carbon fibers is 2:4:4.
[0113] Comparative Example 1
[0114] This comparative example provides a positive electrode plate, which is the same as Example 1 except that it does not include polyvinyl butyral.
[0115] Comparative Example 2
[0116] This comparative example provides a positive electrode plate, which is the same as Example 1 except that the mass of the composite conductive agent is replaced by SP conductive carbon black.
[0117] Comparative Example 3
[0118] This comparative example provides a positive electrode plate, which is the same as Example 1 except that the mass of the composite binder is replaced by PVDF, and the mass of the composite conductive agent is replaced by SP conductive carbon black.
[0119] In the positive electrode sheets described in the above embodiments and comparative examples, the composition of the composite binder and the composition of the composite conductive agent are shown in Table 1.
[0120] Table 1
[0121]
[0122]
[0123] The positive electrode sheets, negative electrode and electrolyte obtained in the above embodiments and comparative examples are prepared into batteries, wherein the negative electrode active material used in the negative electrode is artificial graphite, the electrolyte is a solution of ethylene carbonate + diethyl carbonate + ethyl methyl carbonate containing 1 mol / L LiPF6 electrolyte, and 0.5 vol.% of fluoroethylene carbonate is added.
[0124] The obtained battery was subjected to a room temperature cycle performance test: the charge and discharge potential range was 3.5V to 4.9V, the charging process was constant current 1C to 4.9V, 4.9V constant voltage charging to a cut-off current ≤0.05C, after standing for 5 minutes, 1C discharge to 3.5V, and standing for 5 minutes; the charge and discharge were cyclically performed in this way, and the cycle performance at room temperature (25°C) was tested, and the cycle capacity retention rate after 500 cycles was recorded.
[0125] The test results are shown in Table 2:
[0126] Table 2
[0127] <![CDATA[Positive specific capacity (mAh·g -1 )]]> 500 cycles retention rate (%) Example 1 116.5 80 Example 2 112.4 66.5 Example 3 110.5 65.4 Example 4 113.7 77.2 Example 5 113.9 77.6 Example 6 114.6 72.3 Example 7 115.4 74.6 Example 8 114.7 70.1 Example 9 115.1 71.3 Example 10 109.8 64.9 Embodiment 11 113.2 65.1 Example 12 114.1 71.8 Embodiment 13 113.5 69.1 Comparative Example 1 115.2 62.3 Comparative Example 2 113.1 58.9 Comparative Example 3 113.4 55.7
[0128] From Table 1 and Table 2, we can see that:
[0129] It can be seen from Examples 1-5 and 10-11 that the mass ratio of AS resin and polyvinyl butyral in the present invention is preferably (2:8) to (7:3), and is further preferably (4:6) to (6:4), which can further improve the gram capacity and cycle performance of the battery; It can be seen from Examples 1 and 6-9 and 12-13 that the present invention preferably uses a combination of carbon nanotubes, carbon fibers and porous carbon-graphene composite materials in a specific mass ratio, which can further promote the composite conductive agent and the positive electrode active material to form point, line and surface multi-dimensional contact, forming a complete conductive network, thereby further improving the performance of the battery; It can be seen from Example 1 and Comparative Examples 1-3 that when the composite binder and the composite conductive agent described in the present invention are used in combination, the gram capacity and cycle performance of the battery can be guaranteed.
[0130] In summary, the present invention provides a positive electrode plate and a preparation method and application thereof. The positive electrode plate adopts AS resin and polyvinyl butyral as a composite binder, which can not only effectively bond and protect the positive electrode material from corrosion by the electrolyte, but also improve the mechanical properties of the positive electrode plate, thereby further improving the cycle performance of the battery.
[0131] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode active layer, and the positive electrode active layer comprises a positive electrode active material, a composite binder and a composite conductive agent; The composite binder comprises AS resin and polyvinyl butyral.
2. The positive electrode sheet according to claim 1, characterized in that: The mass ratio of the AS resin to polyvinyl butyral is (2:8) to (7:3).
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The composite conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes carbon nanotubes and / or carbon fibers, and the second conductive agent includes a porous carbon-graphene composite material.
4. The positive electrode sheet according to claim 3, characterized in that: In the composite conductive agent, the content of the second conductive agent is 30-70wt%.
5. The positive electrode sheet according to claim 3, characterized in that: The first conductive agent includes carbon nanotubes and carbon fibers; In the composite conductive agent, the mass ratio of the carbon nanotubes to the carbon fibers is (2:8) to (8:2).
6. The positive electrode sheet according to claim 1 or 2, characterized in that: The lithium de-ionization cut-off potential of the positive electrode active material is ≥4.4V.
7. The positive electrode sheet according to claim 6, characterized in that: The positive electrode active material includes any one of a nickel manganese oxide material, a lithium-rich manganese-based positive electrode material, lithium cobalt oxide or a ternary positive electrode material, or a combination of at least two thereof.
8. The positive electrode sheet according to claim 1 or 2, characterized in that: The mass ratio of the positive electrode active material, the composite binder and the composite conductive agent is (80-97):(1.5-10):(1.5-10).
9. A method for preparing a positive electrode sheet according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) mixing a positive electrode active material, a composite binder, a composite conductive agent and a solvent to obtain a positive electrode slurry; (2) Coating the positive electrode slurry described in step (1) on at least one side of the current collector to obtain the positive electrode sheet.
10. A battery, characterized in that: The battery comprises the positive electrode sheet as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Composite conductive agent laminar coating lithium ion battery positive plate and preparation method thereof
CN107958993A
Composite binder, secondary battery and electric equipment
CN116554815A
Non-fluorine high-adhesion binder and application thereof
CN117431026A
Binder for lithium ion secondary battery negative electrode, negative electrode for lithium ion secondary battery and lithium ion secondary battery using the same
JP2018174038A
